2020
DOI: 10.1097/ta.0000000000002859
|View full text |Cite
|
Sign up to set email alerts
|

Trauma center activity and surge response during the early phase of the COVID-19 pandemic—the Philadelphia story

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 26 publications
(12 reference statements)
11
95
1
2
Order By: Relevance
“…There was a worldwide reduction of between 20.3% and 84.6% in trauma patients compared to a pre-COVID control period. 10 , 11 , 12 , 13 , 14 , 15 , 17 , 19 , 20 , 25 , 27 , 34 , 35 , 37 , 41 , 42 , 43 , 44 , 45 , 46 Hernigou et al 16 reported a concomitant increase in paediatric trauma and reduction in adult trauma during the pandemic at their centre in Belgium, a finding replicated in one Australian centre. 47 Additionally, Wong et al‘s centre based in Australia reported no change in paediatric trauma requiring acute admission.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…There was a worldwide reduction of between 20.3% and 84.6% in trauma patients compared to a pre-COVID control period. 10 , 11 , 12 , 13 , 14 , 15 , 17 , 19 , 20 , 25 , 27 , 34 , 35 , 37 , 41 , 42 , 43 , 44 , 45 , 46 Hernigou et al 16 reported a concomitant increase in paediatric trauma and reduction in adult trauma during the pandemic at their centre in Belgium, a finding replicated in one Australian centre. 47 Additionally, Wong et al‘s centre based in Australia reported no change in paediatric trauma requiring acute admission.…”
Section: Resultsmentioning
confidence: 90%
“…The rise in assaults, domestic violence and NAI is likely a result of the well documented increase in domestic abuse and alcohol consumption. 41 , 69 , 70 Falls from less than 2 m continue to be the most common mechanism of injury in trauma, which generally occur in the elderly. 71 These injuries tend to occur indoors and therefore the stimulus for such injuries remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are aligned with these previous findings. In Philadelphia, there was an increase in gun-related trauma during March 2020, despite overall decrease in trauma encounters in the ED [ 9 , 10 ]. Although their study did not show an increase in overall trauma, penetrating trauma, or NAT among pediatric trauma centers, they highlight the overall increased rates of interpersonal violence that was observed in other major cities in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 surge, we observed the previously described phenomenon where a decrease in surgical volume is compensated by an increase in the number of ICU patients. 6,8 Uniquely approaching the recent COVID-19 surge as a nonsurgical "mass casualty event" a data were available for 60 patients in pre-COVID and 95 patients in the surge group; # data presented for those who were on mechanical ventilation; SD, standard deviation; IQR, interquartile range; APACHE II, Acute Physiology and Chronic Health Evaluation II score; EGS, emergency general surgery ; ICU, intensive care unit; LOS, length of stay; AMA, against medical advice; Acuity 2019 predicted mortality was calculated based on MDN Phoenix database (Medical Decisions Network; Charlottesville, Virginia). 7 helped us to reallocate resources to clinical "hot spots" while continuing to provide adequate coverage across all patient populations managed by the ACS service.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] The COVID-19 pandemic has challenged health care systems and hospitals with an increased demand for both human and material resources and has presented a unique opportunity to test the performance of the ACS model during this nonsurgical catastrophic event. 6 During the COVID-19 surge in Boston from March to May 2020, the ACS service at an urban, tertiary, level I academic trauma center was assigned to continue coverage of all trauma, EGS, and SCC patients, with the added responsibility of taking care of critically ill nonsurgical patients including COVID-19 positive patients.…”
Section: Introductionmentioning
confidence: 99%